JENIS DAN PENYEBARAN BURUNG PADA KAWASAN BANDAR UDARA INTERNASIONAL SULTAN BABULLAH KOTA TERNATE - Prawira, Rahmat; Puttileihalat, Maya; Sahusilawane, John (MARSEGU : Jurnal Sains dan Teknologi, 2024)
This research aims to determine the types and distribution of birds in the Sultan Babullah International Airport area, Ternate City. The research was conducted on January 9-20 2023. Data analysis used the IPA method (Index Pontualle de'Abondance). The research results showed that the types of birds found during the research were 9 species from 7 families. The movement patterns of birds that use grass habitats either in groups or solitary and often in the runway area cause bird strikes in the afternoon. The types of birds found were 235 birds from 2 observation routes with different levels of dominance. Line 1 is dominated by the Sharp-tailed Sandpiper (Calidris acuminata) 33.30%, Swamp Bondol (Lonchura malacca) 31.46%, Garden Fan (Rhipidura leucophrys) 12.34%, Fire Kite (Hirundo rustica) 7.30%, Buffalo Swallow (Motacilla flava) 4.92%, Maluku Swallow (Collocalia infuscata) 4.30%, Eurasian Sparrow (Passer montanus) 4.30%, Cow Swallow (Collocalia esculenta) 1.20% and Eagle (Accipitridae) 0.78%, with a total of 162 individuals. Lane 2 is dominated by Garden Fan (Rhipidura leucophrys) 28.37%, Rawa Bondol (Lonchura flava) 25.68%, Maluku Swallow (Collocalia infuscata) 16.22%, Fire Kite (Hirundo rustica) 13.53%, Eurasian Sparrow (Passer montanus) 9.46%, Buffalo Songbird (Motacilla flava) 6.75%. Eagle and Cow Swallow 0% because they were not found on the second observation route, with a total of 74 birds.